16th International Conference on VLSI Design, 2003. Proceedings.
DOI: 10.1109/icvd.2003.1183171
|View full text |Cite
|
Sign up to set email alerts
|

Interconnect delay minimization using a novel pre-mid-post buffer strategy

Abstract: We consider the problem of minimizing the delay in transporting a signal across a distance in a VLSI circuit.The problem can be restated as a combined buffer insertion, buffer sizing and wire sizing problem. We propose a simple buffering architecture for this problem and show that this architecture achieves a near optimal solution. We also derive simple models for a buffered wire which are suitable for high level design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The related structure is named as "Unequal buffer partitioning network" against "Equal buffer partitioning network" that was mentioned above. The optimum delay is a function of various parameters such as the buffers sizes, the interconnect segments lengths, the load and so on [9], [11], [12], [15]- [17], [19]- [22]. It is shown that for the optimization of a buffer inserted interconnect behavior, the energy-delay product minimization is better than the delay minimization.…”
Section: Repeater Insertion As a Technique For The Delay Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The related structure is named as "Unequal buffer partitioning network" against "Equal buffer partitioning network" that was mentioned above. The optimum delay is a function of various parameters such as the buffers sizes, the interconnect segments lengths, the load and so on [9], [11], [12], [15]- [17], [19]- [22]. It is shown that for the optimization of a buffer inserted interconnect behavior, the energy-delay product minimization is better than the delay minimization.…”
Section: Repeater Insertion As a Technique For The Delay Reductionmentioning
confidence: 99%
“…The repeater (buffer) insertion technique is generally used to reduce the delay of long (semi global) and global interconnects [9], [11]- [16]. An analytical model for obtaining the optimal buffer size and segment length for an equal partitioning network, in which the buffers sizes and segments lengths are constant, has been presented [12], [14], [17].…”
Section: Repeater Insertion As a Technique For The Delay Reductionmentioning
confidence: 99%
“…Therefore placement synthesis and mapping should be considered during synthesis and technology mapping. Once the cell positions are known, the model can be used to accurately predict the interconnect performance [19]. Fig.6 shows delay for three different wire line lengths.…”
Section: Amentioning
confidence: 99%
“…Also various methods have been proposed to reduce the power, which most of them have focused on the switch boxes as a part of interconnects and routing resources [14][15][16][17][18][19][20]. Buffer insertion is one of the most effective methods for improving interconnects' performance, directly reducing delay or reducing delay via reducing crosstalk effects [21][22][23][24][25][26][27]. Most of these methods are easily implemented in ASIC circuits, but it is too complicated to use them in FPGAs.…”
Section: Introductionmentioning
confidence: 99%